Impact of Probiotics and Prebiotics on Gut Microbiome and Hormonal Regulation - Jelina Basnet; Manar A. Eissa; Licy L. Yanes Cardozo; Damian G. Romero; Samar Rezq (Gastrointestinal Disorders)
The gut microbiome plays a crucial role in human health by influencing various physiological functions through complex interactions with the endocrine system. These interactions involve the production of metabolites, signaling molecules, and direct communication with endocrine cells, which modulate hormone secretion and activity. As a result, the microbiome can exert neuroendocrine effects and contribute to metabolic regulation, adiposity, and appetite control. Additionally, the gut microbiome influences reproductive health by altering levels of sex hormones such as estrogen and testosterone, potentially contributing to conditions like polycystic ovary syndrome (PCOS) and hypogonadism. Given these roles, targeting the gut microbiome offers researchers and clinicians novel opportunities to improve overall health and well-being. Probiotics, such as Lactobacillus and Bifidobacterium, are live beneficial microbes that help maintain gut health by balancing the microbiota. Prebiotics, non-digestible fibers, nourish these beneficial bacteria, promoting their growth and activity. When combined, probiotics and prebiotics form synbiotics, which work synergistically to enhance the gut microbiota balance and improve metabolic, immune, and hormonal health. This integrated approach shows promising potential for managing conditions related to hormonal imbalances, though further research is needed to fully understand their specific mechanisms and therapeutic potential.